2004
DOI: 10.2134/agronj2004.3980
|View full text |Cite
|
Sign up to set email alerts
|

Shading and Thinning Effects on Seed and Shoot Dry Matter Increase in Determinate Soybean during the Seed‐Filling Period

Abstract: under drought conditions (Kobata et al., 1992). Both cereal crops clearly change their growth phase from The relationship between seed and shoot dry matter increase (R S/W ) during the seed-filling period (SFP) can reflect the balance between vegetative to reproductive stages, and the potential S the assimilate supply and the sink capacity of harvest organs. In a barely changes once the SFP begins (Evans, 1996). In 2-yr experiment, the R S/W in determinate soybean [Glycine max (L.) soybean, however, active ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There are several reports suggested that increasing population density up to 33.3 or 44.4 plant/m 2 led to a pronounced increase in the plant height (El-Douby et al, 1996 andAbdel-Aziz andShalaby, 1999). On the other hand, Kakiuchi and Kobata (2004) revealed that lower plant density increased faba bean yield attribute i.e. pod number/plant while, the higher plant population decreased the pods number/plant.…”
Section: Introductionmentioning
confidence: 91%
“…There are several reports suggested that increasing population density up to 33.3 or 44.4 plant/m 2 led to a pronounced increase in the plant height (El-Douby et al, 1996 andAbdel-Aziz andShalaby, 1999). On the other hand, Kakiuchi and Kobata (2004) revealed that lower plant density increased faba bean yield attribute i.e. pod number/plant while, the higher plant population decreased the pods number/plant.…”
Section: Introductionmentioning
confidence: 91%
“…The process of soybean flowering, pod formation, and yield formation is also the process of accumulation and distribution of its internal substances. Reasonable and effective biomass accumulation and distribution will increase the number and weight of soybean seeds, which is an important approach for improving soybean yield [22,24]. Researchers usually use different growth parameters to measure the crop's growth trajectory in terms of crop growth rate (CGR), relative growth rate (RGR), and net assimilation rate (NAR) [25].…”
Section: Introductionmentioning
confidence: 99%